Study the Influence of Nonlocal Boundary Condition on the Difference Eigenvalue Problem for Elliptic Partial Differential Equation - El-Mowafy, N.; Helal, S. M.; El-Azab, M. S. (Journal of Informatics and Mathematical Sciences, 2020)
This paper presents a study of the difference eigenvalue problem for elliptic partial differential equations with a differential type multipoint nonlocal boundary conditions. We formulate the stability analysis technique which is based on the spectral structure of the transition matrix which has different types of eigenvalues. We begin by studying the one-dimensional problem and generalize the results to the two-dimensional problems by appropriate difference operators with nonlocal conditions.